PERTANGGUNGJAWABAN NAZHIR ATAS PENGELOLAAN TANAH WAKAF YANG TIDAK SESUAI DENGAN ASAS UU NO 41 TAHUN 2004TENTANG WAKAF(STUDI KASUS DI TANAH MESJID AL-MUHAJIRIN) - Hikmah Fauziah; Hasballah Thaib, Zamaksyari Bin Hasballah, Utary Maharany (INTELIGENSIA MEDIA, 2024)
Management of waqf land is a very important responsibility for the nazhir, which is regulated by Law no. 41 of 2004 concerning Waqf. Waqf plays a crucial role in people's lives, both from a social, economic and religious perspective. The land of the Al-Muhajirin Mosque as an object of study in this context highlights the complexities and challenges that nazhir may face in carrying out their obligations in accordance with the principles established by the waqf law. This research examines the problem, how to apply the principle of legal responsibility to waqf nazhir who manage waqf land, seen from Law no. 41 of 2004 concerning Waqf and Islamic Law? What are the nazhir's obstacles in carrying out his obligations to manage waqf land in terms of Law no. 41 of 2004 Concerning Waqf? What sanctions are given to Nazirs who do not carry out their obligations in accordance with the law? This research method uses a type of normative legal research (normative juridical) which is descriptive analytical in nature. The data sources used in research using the normative juridical approach method are secondary data using legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials using library research data collection techniques and field research, namely a research carried out systematically by collecting existing data in the field. Nazir waqf research results must be held accountable in accordance with Law no. 41 of 2004 and principles of Islamic law. They must carry out their duties carefully, both legally and socially. However, obstacles such as the illegal appointment of the BKM Chair and the lack of human resources at the Al-Muhajirin Mosque can hamper the efficiency of waqf management. Sanctions for nazhir who violate obligations can be in the form of warnings, revocation of mandates, or administrative sanctions such as fines. Mistakes in waqf management can have serious consequences because they involve assets entrusted to them.